Three‐dimensional coronary dark‐blood interleaved with gray‐blood (cDIG) magnetic resonance imaging at 3 tesla. Issue 3 (9th April 2015) - Xie, Guoxi; Bi, Xiaoming; Liu, Jiabin; Yang, Qi; Natsuaki, Yutaka; Conte, Antonio Hernandez; Liu, Xin; Li, Kuncheng; Li, Debiao; Fan, Zhaoyang
Abstract : Purpose: Three‐dimensional (3D) dark‐blood MRI has shown great potential in coronary artery plaque evaluation. However, substantial variability in quantification could result from superficial calcification because of its low signal. To address this issue, a 3D coronary dark‐blood interleaved with gray‐blood (cDIG) technique was developed. Methods: cDIG is based on a balanced steady‐state free precession readout combined with a local re‐inversion‐based double‐inversion‐recovery (LocReInv‐DIR) preparation. The LocReInv‐DIR is applied every two RR intervals. Dark‐blood and gray‐blood contrasts are collected in the first and second RR interval, respectively. To improve the respiratory gating efficiency, two independent navigators were developed to separately gate the respiratory motion for the two interleaved acquisitions. In vivo experiments in eight healthy subjects and one patient were conducted to validate the technique. Results: cDIG provided dual‐contrasts without compromise in scan time. The dark‐blood images with cDIG demonstrated excellent wall and lumen signal performances and morphological measurements. Advantageously, cDIG yielded a second contrast that was shown to help identify the superficial calcification in the coronary plaque of a patient. Conclusion: A novel technique was developed for obtaining 3D coronary vessel wall and gray lumen images. The additional contrast may aid in identifying calcified nodules and thus potentially improve the evaluation of coronary plaque burden. Magn Reson Med 75:997–1007, 2016. © 2015 Wiley Periodicals, Inc.